Body mass index is associated with health-related quality of life and disease characteristics in young adults with juvenile idiopathic arthritis - Anna-Kaisa Tuomi; Katariina Rebane; Ellen Dalen Arnstad; Lillemor Berntson; Anders Fasth; Mia Glerup; Troels Herlin; Hannu Kautiainen; Ellen Nordal; Suvi Peltoniemi; Marite Rygg; Veronika Rypdal; et al. (BMC, 2024)
Abstract Background There is a growing interest concerning the relationship between obesity and several medical conditions and inflammation. Nevertheless, there is a lack of studies regarding body mass index (BMI) among patients with juvenile idiopathic arthritis (JIA). Our aim was to investigate the impact of BMI on health-related quality of life (HRQoL) measured with a 36-Item Short Form Survey (SF-36), disease activity, and disability in young adults with JIA. Methods This study is a part of the population-based Nordic JIA cohort study. All newly diagnosed patients with JIA were recruited consecutively between 1997-2000 in specific regions in the Nordic countries. Patients in this sub-study were enrolled from 434 patients who attended their 18-year follow-up visit. Patients were classified according to the World Health Organization (WHO) into four groups based on their BMI. HRQoL, disease characteristics, disability, fatigue, sleep quality, physical activity, pain, comorbidities, and social status were assessed. Results Three hundred fifty-five patients from the original study cohort were enrolled in this study and 72% of them were female. Mean age was 23.9 (± SD 4.4) years. A significant relationship was found between the JIA categories and BMI groups (p = 0.014). A significant relationship was also found between BMI and disease activity scores (DAS28) (p = 0.028), disability (p < 0.001), pain (p = 0.013), fatigue (p = 0.035), and sleep quality (p = 0.044). Moreover, a significant relationship between BMI and HRQoL regarding bodily pain (p = 0.010) and general health (p = 0.048) was revealed when adjusted for sex, age, and JIA subtype. Conclusion We discovered that BMI was significantly related to HRQoL, disease activity, and disability. BMI deserves more attention considering the treatment options and outcome of JIA in young adults.